A new class of (j; k)-symmetric harmonic starlike functions - AL SARARI, Fuad; SATYANARAYANA, Latha (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
Using the concepts of (j; k)-symmetrical functions we define the class of sense-preserving harmonic univalent functions SHj;ks (β), and prove certain interesting results. Mathematics Subject Classification (2010): 30C45.